Praying for the honor of the Prophet and seeking blessings from the righteous according to the scholars and the position of Sheikh Muhammad Alawi Al-Maliki from his book: Concepts that must be correct - Katih, Ismaie (Al-HIKMAH Journal, 2022)
Abstract This research aims to study issues of begging for the sake of the Prophet, peace be upon him, and seeking blessings from the righteous; To extrapolate the opinion of scholars from it, and the position of Sheikh Muhammad Alawi Al-Maliki through his book Concepts that Must Be Correct; In order to achieve its set goals, the researcher followed the descriptive analytical approach, to discuss the problematic of the subject. After this study, he reached several results: The first: that the sheikh was born in Mecca and one of its nobles, and he is a Maliki school of thought, a Sufi in belief, and a Azhari scholar, but this affiliation did not prevent him from expressing his opinion on the issue of tawassul and seeking blessings from those who pray, as most of the scholars affiliated with Mecca prevent this. Perhaps he was influenced by the opinion of Al-Azhar scholars on this issue. Second: Despite the Sheikh’s mediation in his book and his fairness in presenting the information with evidence, he received responses from some scholars, and among the most famous books that he wrote in response to the famous book “These are our concepts in response to concepts that must be valid.” The third: The scholars’ views and their position on this issue varied. Some of them permitted this to the Prophet and not others, and some of them prohibited it absolutely. Because it is a request for relief and it is for God alone, and a group stood with it the position of detail. Fourth: The position of Sheikh Muhammad Alawi regarding tawassul and seeking blessings is that it is permissible, based on their consideration of tawassul by doing righteous deeds, and it is permissible. Keywords: Tawassul, Tabaruk, the righteous, Al-Yishkh Muhammad Alawi, concepts that must be correct.